Shaking-table tests of seismic responses of slender intake tower-hoist chamber systems. (1st September 2021) - Zhang, Hanyun; Jiang, Cai; Liu, Shuming; Zhang, Liaojun; Wang, Chen; Zhang, Yunjuan
Highlights: A series of shaking-table experiments with incremental earthquakes were conducted. A novel low-strength simulated concrete was developed for the model. DIC and OC technology was used to measure strain field and trace crack development. Natural vibration character, seismic responses and damage progression were tested. Abstract: It is important for the intake tower-hoist chamber systems to resist earthquake loading and function properly immediately after an earthquake. In this study, a series of shaking table experiments with incremental level of earthquakes were conducted to investigate the seismic responses of a 105-m slender intake tower considering the dynamic interactions of hoist chamber-main tower-backfill concrete. According to the similitude law, low-strength simulated concrete was developed for the small-scale intake tower tests. Digital image correlation and conventional measurements were performed to characterize the elastic deformation, damage and failure of the intake tower system subjected to earthquakes with peak ground accelerations of 0.1–0.7 g. The results show that the fundamental frequency is decreased by 48.7% as the peak ground acceleration is increased to 0.7 g, the main tower is disconnected along the through cracks at the junction between the tower and backfill concrete, and the hoist chamber fails with residual deformation. The seismic damage of the hoist chamber initiates earlier and develops more quickly than that of the main tower. The seismic response of the main tower can be significantly affected by the height of the backfill concrete and the connection of joints.